Assessment Knowledge of Diabetic Patients towards Prevention of Diabetic Retinopathy at the Endocrinology and Diabetes Center in Basra City - Khadija Mohammed Jassim; Zainab Salman Dawood; Adil Ali Hussein (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: The study goals to: To assess diabetic patients’ knowledge of diabetic retinopathy (DR), toassess the knowledge of diabetic patients regarding the prevention of diabetic retinopathy and to find out therelationship between the level of knowledge regarding the prevention of diabetic retinopathy and clinicalsocio-demographic characteristics.Methodology: A cross-sectional study design was performed though out the present study for periodfrom 1st December 2020 to 20st March 2021. A non - probability purposive sample of 100 patients at theEndocrinology and Diabetes Center in Basra City. Data were collected through the questionnaire constructedand the self-management reporting process. The questionnaire consists of three parts: social and clinicaldemographic characteristics (age, gender, marital status, educational level, occupation, the environment,economic Status, duration of illness, type of diabetes mellitus, A family history of diabetes, type of treatmentfor diabetes and history of eye disease).The second part consist of questionnaire contain questions relatedto general information regarding knowledge of diabetic patients about diabetic retinopathy. The third partcontains questions related to the prevention of diabetic retinopathy in patients with diabetes. The validityof the tool content was determined by a committee of experts, and the internal consistency of the tool wasdetermined through a pilot study and the calculation of the alpha correlation coefficient (r = 0.70). Analyzingdata by descriptive and inferential statistical approaches using (SPSS) version 22.0.Results: The results of the study showed that (55%) had a poor level of knowledge regarding diabeticretinopathy, and (50%) had a moderate level of knowledge regarding the prevention of diabetic retinopathy.